The Methodology of Imam Badr al-Din Ibn Qadi Shuhba (d. 874 AH) in Reasoning with the Sunnah in his Book Bidayat al-Muhtaj fi Sharh al-Minhaj - Tariq Saleh Hazam,; Zainab Ibrahim Hussein, (Islamic Sciences Journal, 2025)
This research aims to introduce Imam Badr al-Din Ibn Qadi Shahba and his book, Bidayat al-Muhtaj fi Sharh al-Minhaj, as well as his methodology in reasoning with the Prophetic Sunnah within his book. Ibn Qadi Shuhba is counted among the later imams of the Shafi‘i school and was a scholar who left a significant mark on Shafi‘i jurisprudence. Yet, many students and researchers are unaware of his scholarly rank and contributions. This called for a systematic academic study that highlights the imam, his book, and his manner of deducing from the Sunnah and the noble Hadith. The first section of this study introduces the author and his book. The second section discusses the methodology he followed in reasoning with the Sunnah, which he regarded as the second source of Islamic legislation, showing how he employed Hadiths and reports in constructing legal rulings. His methodology gave his work enduring value, making it a book that no jurist or student of knowledge can dispense with, and establishing it as a scholarly reference in Islamic and Shafi‘i jurisprudence